RECONSTRUCTION OF NATIONAL IDENTITY WITH THE ONSET OF THE WAR IN UKRAINE - Eugen Bruno ȘTEFAN (International Journal of Social and Educational Innovation, 2023)
The conflict in Ukraine has triggered a process of rebuilding the self-image of most Romanians. Massive support for refugees has shown others, but also for themselves, that Romanians help their neighbours when they run into difficulties, that they sacrifice their goods and time, and even their security to support those with whom they had disagreements in the past. The Bureau of Social Research survey highlights the reasons for this identity narrative that puts at its core social virtues such as tolerance, love, heroism, sacrifice. Compared to the old identity narrative that highlights resentment, self-contempt, submission to any stranger, betrayal of any principles, values, or allies, the BCS survey shows a profound change that can have consequences on many aspects of social life.